Make, buy, or ally: A transaction cost theory meta-analysis - GEYSKENS, Inge (Institutional Knowledge at Singapore Management University, 2006)
Since the publication of Williamson's Markets and Hierarchies, many empirical articles have investigated the tenets of transaction cost theory. Using meta-analytic techniques, we quantitatively synthesized and evaluated transaction cost-based empirical research on organizational boundary (make, buy, or ally) decisions. We found strong support for the theory for both make versus buy and ally versus buy decisions. However, we did not find evidence that asset specificity had stronger predictive power than uncertainty. Hierarchical and relational governance appropriately aligned with transaction dimensions both led to enhanced performance. On the basis of our meta-analysis, we provide directions for future research.